Dermatophytosis: Clinical and therapeutic study in a reference center in the eastern Amazon - Pires,Carla Andrea Avelar (2022)
Abstract Introduction: Dermatophytosis is the most common fungal infection of the skin, hair, and nails in humans. It affects about 20% of the world's population in all age groups. Objectives: To analyze clinical, epidemiological, and therapeutic characteristics of patients diagnosed with dermatophytosis treated at a general and tropical dermatology reference service in the Brazilian Amazon region. Methods: We analyzed 75 medical records from January 2016 to January 2020, with a researchers' protocol to collect data on clinical forms, treatment, and recurrence. Statistical analysis used the chi-square test of adherence, and p < 0.05 was considered statistically significant. Results: There was a female predominance, mean age of 49 years and 28% of patients had more than 10 lesions. The dominant type of dermatophytosis was onychomycosis in adults, followed by Tinea capitis (24%) in the pediatric group (mean 11.39 years). The elderly (37.33%) and children (26.67%) were the most affected. In most cases, treatment with combined topical and systemic medications was chosen. Griseofulvin and terbinafine were the most prescribed for systemic treatment and ciclopirox olamine was the main prescribed topic (36%). Although 77.3% of the patients attended a follow-up appointment, 25.33% relapsed in less than one year. Conclusion: The analyzed data emphasizes the importance of early diagnosis and treatment of dermatophytosis, especially in the extreme age group —pediatric and elderly age groups— besides the active importance of non-pharmacological measures to reduce recurrences and morbidity for patients.